Degradation of cytarabine, creatinine, and urea in artificial urine by a photo-assisted sono-electrochemical process (Research, Society and Development, 2020)
The present work had as its objective, the evaluation of the combination of electrochemical, photochemical and sonrochemical techniques (sono-electrochemical photoassisted) applied to degradation of cytarabine (chemotherapeutic drug) in a simulated urine that continues with creatinine and laboratory research. The paper involved laboratory research with both a qualitative and quantitative approach. A continuous-flow filter-press electrochemical reactor was employed using Dimensionally Stable Anode (DSA® - Ti/Ru0.3Ti0.7O2) as the electrode material. A 23 factorial design was used to optimize the degradation of organic compounds contained in artificial urine (creatinine and urea) together with cytarabine, varying applied current, retention time and flow rate, the response variable was total organic carbon (TOC) removal. Additionally, UHPLC analyses demonstrated the removal of ancitabine (precursor of cytarabine), corroborating with the data obtained by the from the experimental design. The use of artificial urine as an electronic support interferes with the electrochemical process, taking TOC to high levels. However, it was observed that there was significant removal of the organic load present in the effluent solution, even when a more complex degradation matrix is used (artificial urine).